The Impact of Internal Auditing on Risk Management Disclosure - WANG, YUNHE (2017)
This dissertation investigates the impact of internal auditing (i.e., internal auditing size, audit expertise) on risk management disclosure in China A-share companies listed in Shenzhen Stock Exchange from the 2013-2015. The empirical results support the significant role of internal auditing in motivating Chinese firms to exhibit higher levels of disclosure about risk management in the narrative sections of their annual reports. It shows that firms characterised by larger internal audit sector, the more frequent communication with audit committee and external auditor and which are able to disclose internal control report are likely to exhibit significantly higher levels of risk management disclosures. The results also reveal that firms with lower profitability are more willing to disclose risk management information in order to cover the shortage of operation and show their management ability. The results further suggest that auditors of firms should strengthen continuing education. On the other hand, company should also be valued on directors’ independence. This dissertation further researches the impact of a general provision of the annual internal control evaluation report published in 2012 on internal audit quality.